The disappearing spoon [compact disc, unabridged] : and other true tales of madness, love, and the history of the world from the periodic table of the elements - Kean, Sam (Tantor Audio, 2010)
The periodic table is one of man's crowning scientific achievements. But it's also a treasure trove of stories of passion, adventure, betrayal, and obsession. The infectious tales and astounding details in The Disappearing Spoon follow carbon, neon, silicon, and gold as they play out their parts in human history, finance, mythology, war, the arts, poison, and the lives of the 'frequently' mad scientists who discovered them.